Peningkatan Kepercayaan Nasabah Tabungan Mudharabah melalui Pendekatan Syariah Marketing, Service Excellence, dan Reputasi - Halimah, Anis (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
Customer trust is one of the keys for BMT to raise funds in Mudharaba savings. Many factors to influence the trust of these customers. Among them are sharia marketing, service excellence and reputation. This study analyzes the influence of the three factors on customer trust to save their fund in mudharaba savings. This research collected interview results to 75 Customer Mudharaba savings in BMT Zam Zam Sragen with questionnaire. The data had been analyzed by multiple linear regression analysis using SPSS for Windows Release 23.0. The results show that Customer Trust to save in Mudharabah savings is positively and significantly affected by sharia marketing and service excellence and reputation. The research gives a contribution to (a) academician; as an evidence of theory, (b) BMT; information to analyze the factors that affect Costumer Trust to save their fund in Mudharaba savings.